Regulatory gene function handoff allows essential gene loss in mosquitoes - Cheatle Jarvela, Alys M. (Commun Biol, 2020)
Regulatory genes are often multifunctional and constrained, which results in evolutionary conservation. It is difficult to understand how a regulatory gene could be lost from one species’ genome when it is essential for viability in closely related species. The gene paired is a classic Drosophila pair-rule gene, required for formation of alternate body segments in diverse insect species. Surprisingly, paired was lost in mosquitoes without disrupting body patterning. Here, we demonstrate that a paired family member, gooseberry, has acquired paired-like expression in the malaria mosquito Anopheles stephensi. Anopheles-gooseberry CRISPR-Cas9 knock-out mutants display pair-rule phenotypes and alteration of target gene expression similar to what is seen in Drosophila and beetle paired mutants. Thus, paired was functionally replaced by the related gene, gooseberry, in mosquitoes. Our findings document a rare example of a functional replacement of an essential regulatory gene and provide a mechanistic explanation of how such loss can occur.